Probing the heart and mind of the viewer: scientific studies of film and theatre spectators in the Soviet Union, 1917-1936 - Toropova, Anna (ASEEES, 2018)
A vast array of research institutes and cultural organizations began to study the viewer of Soviet cinema and theatre in the years following the October Revolution. These investigations called on the techniques of sociology, psychology, and physiology to make Soviet cultural production more “efficient” and “rational.” Belying the conventional assumption that the cultural revolution of 1928–1932 brought empirical research in aesthetics to an abrupt end, this paper traces the continuation and redefinition of studies of the viewer in the Soviet Union after the “Great Break.” My analysis of the work of the “Scientific Research Sector” at the State Institute of Cinematography (VGIK) between 1933 and 1936 outlines how Stalin-era researchers shifted their gaze from viewers’ tastes and attitudes to questions of perceptual management and effectiveness. Exploring the VGIK researchers’ attempts to determine the “laws” of aesthetic perception and optimize intelligibility, the article brings to light the developments in scientific knowledge underwriting Soviet culture's transition to a form “accessible to the millions.”